2015
DOI: 10.3402/qhw.v10.28104
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of adolescents with sickle cell disease in Kingston, Jamaica

Abstract: AimTo explore the lived experiences of adolescents with sickle cell disease, in Kingston, Jamaica.MethodA descriptive qualitative design was used for this research. In-depth interviews were conducted with six adolescents with sickle cell disease at a Sickle Cell Unit operated by the University of the West Indies. Interviews were audiotaped, transcribed, and thematically analyzed.ResultsThe majority of the adolescents demonstrated a positive self-concept. They reported strong family, school, and peer support wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 44 publications
6
50
0
3
Order By: Relevance
“…As no study has reported self‐management recommendations from the perspectives from health professionals, there are no studies to provide comparison with the current findings. However, the findings for preventive health are similar to research findings on self‐management recommendations and practices from patients and relatives' perspectives in the United States, Brazil, and Jamaica, as well as recommended measures for healthy living and crisis prevention for SCD management …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…As no study has reported self‐management recommendations from the perspectives from health professionals, there are no studies to provide comparison with the current findings. However, the findings for preventive health are similar to research findings on self‐management recommendations and practices from patients and relatives' perspectives in the United States, Brazil, and Jamaica, as well as recommended measures for healthy living and crisis prevention for SCD management …”
Section: Discussionsupporting
confidence: 77%
“…However, the findings for preventive health are similar to research findings on self-management recommendations and practices from patients and relatives' perspectives in the United States, Brazil, and Jamaica, as well as recommended measures for healthy living and crisis prevention for SCD management. 3,5,7,[38][39][40]47,48 The findings indicate that recommendations for self-monitoring and diagnosis, using objective methods and measurements such as thermometers, splenic palpation, and self-assessment tools, are limited in the Ghanaian health professionals' recommendations. In contrast, researchers of SCD self-management in the United States have focused on objective measurements for pain self-monitoring to understand pain frequency, characteristics, related symptoms, and home management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…93, 94 53,68,70,104,105,108-112 Symptoms become more of a concern when they lead to physical and mental changes or affect the ability of young people to engage in daily activities. 47,54,63,66,81,104,108,109,113…”
Section: Physical Symptoms and Concernsmentioning
confidence: 99%